Biomechanics Analysis And Optimization Of Instep Kicking: A Case Study To Malaysian Footballer - Ahmad Rasdan, Ismail (2010)

(untitled)
This study will focus on the biomechanics analysis on the professional soccer players as well as to identify and investigate problems regarding their kicking action. Analysis would be made by studying on kicking technique using the instep kick which takesicloser look at a professional player in the malaysian league classified at underage of 23 years. In this context, biomechanical analysis has been used to identify the variable such as velocity, acceleration, distance and the angle of the knee whether it would influence the players kicking force. Data management and analysis adapting Silicon Pro Coach software whereas statistical analysis was carried out using Minitab's software. Image of instep kicking was captured during the study and is useful to get the data of the kicking action for the analysis purpose. Based on the findings, the variables was identified to be significant to the force model besides succeeded to obtain the force equation model. Through readings gathered from the Taguchi's method we managed to get the optimum kicking value. Based on the findings, the velocity and distance was identified to be significant with the force model. The highest average force of kicking is 5879.60N that is on the highest average velocity 8.2m/s with distance kick that hit until 47.85m. From Taguchi's method, the optimum distance and velocity namely respectively as much as 0.163m and 8.035m/s can give the highest optimal force to the reading of 5602.12N.